Breaking bending limit of difficult-to-form titanium tubes by differential heating-based reconstruction of neutral layer shifting. (July 2021) - Yang, Heng; Li, Heng; Ma, Jun; Li, Guangjun; Huang, Dan
Abstract: Achieving small-radius bending of difficult-to-form tubular materials with large-diameter, thin-walled (LDTW, D / t  > 20) geometry — as well as the properties of high-strength poor-hardening (HSPH) — is a continual target and challenging issue in the aerospace, marine, and healthcare industries. Based on the theoretical analysis of neutral layer shifting reconstruction (NLSR) by positively utilizing the temperature-dependent tension-compression (T-C) asymmetry of tubes, an innovative differential heating-based rotary draw bending (DH-RDB) method is designed, i.e., applying differential working temperatures at the intrados ( T in ) and extrados ( T out ) of tubes during forming to proactively coordinate the non-uniform deformation and thus prevent multiple forming defects to break the bending limit. To verify the above concept, the temperature-dependent evolution of the T-C asymmetry of titanium tubes was characterised — using commercial pure titanium (CP–Ti) tubes as case materials — and numerically implemented into the thermo-mechanical coupled three-dimensional finite element (3D-FE) model of the DH-RDB process. The influence of two heating schemes–i.e., overall heating and differential heating at the extrados and intrados of the tube — on bending formability was quantitatively assessed regarding multiple bending defects, such as wrinkling, over-thinning, and cross-section flattening. It was found that by introducing differential heating, the design and optimisation space for NLSR in tube bending is enlarged. The overall heating increases the work hardening of titanium tubes and thus restrains wrinkling during bending. Furthermore, the coupling effects of the increased compression-tension flow stress ratio (CTFSR) and decreased friction force under differential heating of T in  <  T out slightly aggravated the inward neutral layer shifting (NLS) but reduced wall-thinning and cross-section flattening. Following the above critical understanding, a series of carefully designed bending experiments were conducted to validate the capability of the DH-RDB to break the bending limit. This proves that the differential heating-based NLSR can be used to positively coordinate T-C non-uniform deformation to break the bending limit of difficult-to-form tubular materials. Graphical abstract: Image 1 Highlights: A differential heating-based rotary draw bending method is designed to proactively coordinate the non-uniform deformation. The temperature dependent tension-compression asymmetry of titanium tubes is characterized and numerically implemented. Coupling of increased compression-tension stress ratio and decreased friction force aggravates inward neutral layer shifting.